The Book of the Covenant: its Literary Setting and Extra-Biblical Background - Paul, Shalom Morton
Ph.D.; Supervisor: E. A. Speiser; University Microfilms Order No. 65-13,367. Microfilm $3.00; Xerography $9.25; Dissertation Abstracts 26/7 (Ann Arbor, Mich., January 1966) 3967-3968; passim zu sum., bab., mA, heth. Gesetzen.